2004
DOI: 10.1177/154405910408301s08
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum of Dental Caries—Evidence for a Dynamic Disease Process

Abstract: The eventual outcome of dental caries is determined by the dynamic balance between pathological factors that lead to demineralization and protective factors that lead to remineralization. Pathological factors include acidogenic bacteria, inhibition of salivary function, and frequency of ingestion of fermentable carbohydrates. Protective factors include salivary flow, numerous salivary components, antibacterials (both natural and applied), fluoride from extrinsic sources, and selected dietary components. Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
441
0
32

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(475 citation statements)
references
References 23 publications
2
441
0
32
Order By: Relevance
“…22,23 Our BAG-containing adhesives have previously shown calcium ion-release into surrounding solution. 20 This study evaluated the potential use of these novel BAGcontaining orthodontic bonding agents for the prevention of WSLs.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Our BAG-containing adhesives have previously shown calcium ion-release into surrounding solution. 20 This study evaluated the potential use of these novel BAGcontaining orthodontic bonding agents for the prevention of WSLs.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries is a dynamic process 1) , progressing from an initial subclinical lesion, through an early clinical detection phase, to cavitation 2) . The management of dental caries has evolved to early clinical detection of initial lesions and using products inducing remineralization to stop lesion progression and reverse surface demineralization before cavitation occurs 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Various investigators reported that early carious lesions can be re-mineralized from saliva. This process was studied in details in laboratory experiments and in clinical trials (1)(2) .…”
Section: Introductionmentioning
confidence: 99%